2014
DOI: 10.1002/anie.201409376
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle‐Mediated Binning and Profiling of Heterogeneous Circulating Tumor Cell Subpopulations

Abstract: The analysis of circulating tumor cells (CTCs) is an important capability that may lead to new approaches for cancer management. CTC capture devices developed to date isolate a bulk population of CTCs and do not differentiate subpopulations that may have varying phenotypes with different levels of clinical relevance. Here, we present a new device for CTC spatial sorting and profiling that sequesters blood-borne tumor cells with different phenotypes into discrete spatial bins. Validation data are presented show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
141
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(141 citation statements)
references
References 28 publications
0
141
0
Order By: Relevance
“…Few studies to date have reported a close relationship between aneuploidy and tumor metastasis. CTCs identified based on the EpCAM staining detection method were closely related to epithelial-mesenchymal transition (EMT) [28] and served as an independent prognostic factor for tumor metastasis [29]. The relationship between CTCs and tumor metastasis should be assessed based on the detection method.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies to date have reported a close relationship between aneuploidy and tumor metastasis. CTCs identified based on the EpCAM staining detection method were closely related to epithelial-mesenchymal transition (EMT) [28] and served as an independent prognostic factor for tumor metastasis [29]. The relationship between CTCs and tumor metastasis should be assessed based on the detection method.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, most of liquid biopsy approaches for CTCs are based on the use of the epithelial cell adhesion molecule (EpCAM) antibodies to capture the CTCs and their subsequent characterization with immunostaining or retro-transcription polymerase chain reaction 10–13 . Some methods employ the intrinsic differences in shape, size and/or density of the tumor cells as compared with the normal circulating cells to collect and later recount CTCs by using filters 1416 , micro-obstacles and gravity 17 , activated surfaces 1820 or particles 15, 2022 . Several CTC detection systems are commercially available and most of them rely on immunomagnetic separation strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Velocity valley and magnetic ranking microfluidic technologies 114119 (Fig. 3D) isolate magnetic affinity-labelled CTCs in different zones of the device depending on antigen (e.g., EpCAM 114119 HER2, 114,117 EGFR, 117 , MUC1, 114 N-Cadherin 118 ) expression level, thus correlating disease progression with CTC phenotype, 114,118 similar to CTC immunophenotyping 29 and RNA-ISH analysis.…”
Section: Magnetic Affinity-selection – From Cellsearch™ To Microflmentioning
confidence: 99%
“…Whole blood, 114118 RBC lysed blood, 117,118 or RBC lysed and WBC-depleted blood 117,119 was spiked with Ab-coated 114116,118 or aptamer-coated 117,119 (discussed below) magnetic nanoparticles. The sample was infused through a series of microfluidic chambers, and an external magnetic field pulled both free magnetic nanoparticles and labelled CTCs onto the device surface.…”
Section: Magnetic Affinity-selection – From Cellsearch™ To Microflmentioning
confidence: 99%